What's emotion got to do with it? Reflections on the buildings of the Portuguese (Family) Courts - Branco, Patrícia (Frontiers in Sociology, 2024)
Courthouses, as public edifices, serve as the physical backdrop for the administration of justice. Simultaneously, they are spaces inhabited and visited by a diverse array of court users, ranging from judicial professionals to litigants. This article explores the nuanced interplay between courthouse spaces and the emotional experiences they generate. It starts by surveying existing studies that examine such an intricate relationship. Then, and by drawing from a sample of interviews conducted across two distinct time periods (2010-2011 and 2017-2019) in Portugal, the article delves into the lived experiences of judges, prosecutors, and litigants. Their narratives provide a multifaceted view of the emotional experiences associated with the Portuguese (Family) Court buildings. To analyse these experiences, I turn to Henri Lefebvre's concept of lived space. Lived space refers to the emotions, memories, and interactions within a particular spatial context. Such dimension, in relation to courthouses, directly connects to the lived experience of legitimacy loss and low self-esteem affecting decision-making, on the one hand, and estrangement and rights' exclusion, on the other hand, felt by those subjects. By investigating how the spatial configurations of courthouses shape our emotions, we gain insights into the profound impact of such built environments on our understanding of the justice system, and the physical and symbolic obstacles in accessing it.